2016
DOI: 10.1002/mbo3.319
|View full text |Cite
|
Sign up to set email alerts
|

Identification and antimicrobial resistance prevalence of pathogenic Escherichia coli strains from treated wastewater effluents in Eastern Cape, South Africa

Abstract: Antimicrobial resistance (AMR) is a global problem impeding the effective prevention/treatment of an ever‐growing array of infections caused by pathogens; a huge challenge threatening the achievements of modern medicine. In this paper, we report the occurrence of multidrug resistance (MDR) in Escherichia coli strains isolated from discharged final effluents of two wastewater treatment facilities in the Eastern Cape Province of South Africa. Standard disk diffusion method was employed to determine the antibioti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
96
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 128 publications
(102 citation statements)
references
References 51 publications
6
96
0
Order By: Relevance
“…E. coli, Shigella, Salmonella and Vibrio spp. have been the predominant pathogens linked to waterborne outbreaks in Africa [21,22], whereas certain clonal strains of these pathogens have been reported to survive conventional wastewater treatment processes [23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…E. coli, Shigella, Salmonella and Vibrio spp. have been the predominant pathogens linked to waterborne outbreaks in Africa [21,22], whereas certain clonal strains of these pathogens have been reported to survive conventional wastewater treatment processes [23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…Normal bacterial flora like E. coli is usually used as an index of transmission and spread of the gained resistant determinant (Adefisoye and Okoh, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Actually, a great prevalence of decreased response to antibiotics is usually recorded in screening assays of different bacterial strains (Shears, 2001), and in researches that examined normal bacterial flora as an important index for distribution of genes that are responsible for decreased response to antibiotics (Alves et al, 2014). In addition, developing localities usually suffer from the bad impact of antibiotic resistance on disease outcome and rates of mortality which is due to recurrent infections by bacteria and the great value of antibiotics in fighting them (Adefisoye and Okoh, 2016). Treatment of many human diseases was greatly dependent on sulphonamid drugs, but, sulphonamides were usually added to trimethoprim in order to decrease the appearance of resistance, this usually limits the prescription of these drugs that have the advantage of being low cost.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, research has shown a lack of correlation in the presence of viral pathogens and faecal indicator bacteria [9,10] whose sole presence or absence cannot be used to accurately predict the presence of other pathogens such as protozoan parasites and enteric viruses which are highly infectious in low doses [11]. Most sewage treatment plants fail to completely remove enteric viruses from wastewater either due to the resistance of viruses to adverse conditions or simply because the treatment plants are generally not designed to remove viral pathogens as they are to reduce the biochemical oxygen demand levels of the wastewater [12]. In South Africa, wastewater in rural areas and small towns often receives partial or minimal treatment [13,14].…”
Section: A Rt I C L E I N F O Abstractmentioning
confidence: 99%
“…The viral nucleic acids were concentrated by the adsorptionelution method of Haramoto et al [22] as modified using a negatively charged Millipore filter membrane (Merck, Ireland) [12]. Briefly, …”
Section: Concentration Of Virusesmentioning
confidence: 99%